Effect of supplementation with barley and calcium hydroxide on intake of Mediterranean shrubs by goats - Rogosic, Jozo; Saric, Tomislav; Herceg, Nevenko; Zjalic, Slaven; Stanic, Svjetlana; Skobic, Dragan (ITALIAN JOURNAL OF ANIMAL SCIENCE, 2011)
Maquis plant communities are one of the most varied vegetation types in the Mediterranean region and an important habitat for wild and domestic herbivores. Although the majority of these shrubs are nutritious, the secondary compounds are the main impediments that reduce their forage value. In five experiments, we determined the effect of supplementing the diets of goats with calcium hydroxide plus barley and with barley alone on their intake of five dominant shrubs (Quercus ilex, Erica multiflora, Arbutus unedo, Viburnum tinus and Pistacia lentiscus) of the Mediterranean maquis community. The combination of calcium hydroxide plus barley and barley alone increased the utilisation of Q. ilex, E. multiflora and P. lentiscus, while the intake of A. unedo and V. tinus was not statistically significantly different. Calcium hydroxide and barley (energy) enhance the use of secondary compound-containing plants, which may increase the production of alternate forages and create a more diverse mix of plant species in the Mediterranean maquis plant community.
The following values have no corresponding Zotero field: pub-location: MEDITGROUP, VIA G BELLI, 4, PAVIA, 27100, ITALY publisher: PAGEPRESS PUBL
Keywords: barley; Calcium hydroxide; Food preference; Goat; Secondary compound